Peripheral and Central Nervous System Immune Response Crosstalk in Amyotrophic Lateral Sclerosis - Liu, Zhouyang; Cheng, Xi; Zhong, Shanshan; Zhang, Xiuchun; Liu, Chang; Liu, Fangxi; Zhao, Chuansheng (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by muscle weakness due to degeneration of the upper and lower motor neurons. Neuroinflammation is known as a prominent pathological feature of ALS. Although neuroinflammation cannot trigger ALS, pro-inﬂammatory periphery monocytes/macrophages and T lymphocytes, activated central nervous system (CNS) microglia, infiltrated monocytes/macrophages and T lymphocytes, as well as the immunoreactive molecules they release, are closely related to disease progression. The crosstalk between the peripheral and CNS immune components mentioned above significantly correlates with survival in patients with ALS. This review provides an update on the role of the crosstalk between the peripheral and CNS immune responses in ALS. Additionally, we discuss changes in gut microbiota composition that can directly or indirectly influence this crosstalk. These recent advances appear to provide great potential for researchers in targeting molecules associated with this crosstalk and breaking the current treatment impasse of ALS.